The Use of Information and Communication Technology (ICT) Tools in Decision Making - Noreha, Mohamed Yusof (2003)
The rapid and pervasive growth of Information and Communication Technology (ICT) has forced organizations worldwide to consider the role of ICT in supporting their business goals. Malaysian business organizations now realize the effective use of ICT to support organized operation activities and the ability to compete. There have been many studies to determine the use of ICT in decision making. However, the importance of ICT in decision making is still not well established especially in Malaysia. This report describes the profile of ICT utilization among 64 business organizations listed in the Kuala Lumpur Stock Exchange (KLSE) 2002: the impacts of ICT on companies’ activities, the perceived roles of ICT in decision making, the extent of ICT application in decision making, the relevant training needed, and also the factors associated with the applications of ICT in a company. This study reveals that the development of ICT especially in the private sector is rapidly growing. The monthly ICT usage among managerial personnel was around 70 percent. Support from top management, incentive from the government, data support, team working and friendly output format are the factors perceived to help promote the use of ICT in decision making among the respondents.